Quench localisation in SRF cavity tests with transition edge sensors. (April 2019) - Furci, H; Vandoni, G; Macpherson, A; Barriere, S; Castilla, A; Shipman, N; Turaj, K; Wartak, M; Zwozniak, A
Abstract: Transition edge sensors (TES) have recently been developed at CERN as second sound detectors for quench localisation on superconducting radio frequency (SRF) cavities. After validation of the concept of heat source localisation by TES in the laboratory, TES have been implemented as a diagnostic tool in SRF vertical testing cryostats at CERN SM18 facility. Two cavities were forced to quench by applying sufficiently high values of RF power. Simultaneously, RF and TES second sound signals were recorded. In this paper we present the particularities of each of the relevant tests, the nature of the read signals, as well as the analysis performed on them to locate the origin of the quenching spot.